Evaluating students' perception of Scrum through a learning game - Rodríguez, Guillermo Horacio (2022)
Games for learning help students and professionals to incorporate new knowledge through a playful experience. With the popularization of virtual education (partially due to COVID-19), there is a need for new tools that complement virtual educational environments. To deal with this need, we present Scrum Game, a mobile application game that aims to support the Scrum software methodology teaching and training. Scrum Game offers 42 activities grouped in levels with specific learning goals. This paper reports on a controlled experiment that evaluates Scrum Game in a course with more than 160 students. We assessed Scrum Game's effectiveness in terms of (i) user performance (i.e., students' marks and number of levels/activities completed) and (ii) user experience (i.e., usability). We found that students who used Scrum Game outperformed those who did not use it. We also found that students think that Scrum Game exhibits an enjoyable user experience.